Covid-19, Competence and Resilience Fresh Graduate of college - Sri Budi Kasiyati; Endang Setyowati; Rudy Santoso (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
Covid-19 is a pandemic that is uncertain when it will end. This study aims to determine the factors of resilience during the Covid-19/Coronavirus Pandemic. This study used a crosssectional design, with purposive snowball sampling. Primary data collection is carried out for one semester starting in August 2021. Respondents fill out a questionnaire about individual characteristics, competencies, Covid-19 experience, and resilience. Resilience was measured using the 10-item Connor-Davidson Resilience Scale and Competence was assessed using five indicators. Respondents who participated in this study were 49 fresh graduates. Regression analysis was carried out to determine the relationship between the variables of resilience, and competence during Covid-19. Competence, statistically positive and significant relationship with Resilience.Competence can explain greater variance in the Resilience of fresh graduate of collegeKey words : Resilience; Competence; Covid-19